Lysogenic System of Non-Epidemic Cholera Vibrio El Tor, Resistant to Diagnostic Bacteriophage CTX- - M. V. Ovchinnikova; G. I. Korovkina; I. V. Gracheva; T. V. Alenkina (Проблемы особо опасных инфекций, 2012)
Studied are non-epidemic strains of V. cholerae O1 biovar El Tor taken from the National collection of pathogenic bacteria lodged at the Russian Research Anti-Plague Institute Microbe, which were not sensible to diagnostic cholera bacteriophage El Tor ctx- at the time of isolation. Represented are the results of investigation regarding a cause of a phage-resistance of these cultures using specialized test-system consisting of indicator strains. Identified is the carriage of temperate phages among 88,0 % of the cultures examined.